Revalorización de la Cuenta Vehículos: Patrulleros Policiales de la Subzona de Policía Los Ríos - Barragán Cando, Lilia Maribel (2020)
The Los Ríos No.12 Police Subzone has a Decentralized Operational Entity (EOD) called the Financial Department and its Fixed Assets Area, whose function is the administration of public goods, where we will develop the present case study of the topic “Revaluation of the Vehicles Account: Patrol Vehicles ”. In the first instance, the person in charge of Fixed Assets was interviewed, where the problem regarding unreliable accounting information in the vehicle account ledgers was determined, for which reason the application of the revaluation process to the assets of the sector is proposed. public, since the useful life of the vehicles has already ended, so it is necessary to revalue to ensure their book value compared to the market price, for this process a technician in order to the technical characteristics of the vehicles will propose new book value in In relation to the market, this value will have its accounting treatment. Within the provisions issued by the General State Comptroller's Office, a revaluation process must be carried out every 5 years depending on the market price and the current condition of the goods, according to the Government Accounting Regulations in force and issued by its governing body, Ministry of Public Economy and Finance.